Anaerobic threshold - a relative useless concept for coaching - Billat, L. V. (1996)
This article contains a very concise summary of the concept of anaerobic threshold and how it is depicted in the literature. The implications of each individual statement are particularly important given the pre-occupation of many coaches with this concept. The major points of the article are discussed below.